Evaluation of recombinant sporozoite antigen SPAG-1 as a vaccine candidate against Theileria annulata by the use of different delivery systems - Boulter, N.; Brown, D.; Wilkie, G.; Williamson, S.; Kirvar, E.; Knight, P.; Glass, E.; Campbell, J.; Morzaria, S.P.; Nene, Vishvanath M.; Musoke, A.J.; Oliveria, C. de; et al. (Wiley, 1999)
The major sporozoite surface antigen of Theileria annulata (SPAG-1) is a candidate for inclusion in a subunit vaccine. In this paper we summarize the results of 4 vaccination experiments using recombinant SPAG-1 expressed in different systems and presented in different adjuvants. The antigen has been presented as either a C terminal 108 amino acid peptide (called SR1) expressed as both beta-galactosidase and hepatitis B core antigen fusions or as a full-length form expressed as a GST fusion with an N terminal His6 tag. Different adjuvants, namely Freund's, saponin, ISCOMs and a proprietary adjuvant supplied by SmithKline Beecham were used, which are called SKBA. The data point to the conclusion that SPAG-1 can elicit partial protection and is therefore suitable for inclusion in an eventual multicomponent subunit vaccine.